JAWI'S WRITING AS A MALAY ISLAMIC INTELLECTUAL TRADITION - Masyhur Dungcik (Journal of Malay Islamic Studies, 2017)
Jawi writings began to show their role in the Malay Land since the entry of Islam into the archipelago. However, at this time Jawi writings seem to have been marginalized by Rumi or Latin writings. This condition is inversely proportional to what happens when Malay (Jawi writing) reaches a high level in its time. At that time Christian priests had to translate the Bible into Malay so they could spread their religion in Malay lands. Whereas at present, Muslims must transliterate the Qur'an into Latin letters so that Muslims can read it in Malay lands. This fact shows that the Malays have experienced a setback in the intellectual tradition that was once possessed in the form of Jawi writing. This research aims to find out the role of Jawi writings in the past and what must be done to safeguard one of the valuable intellectual traditions of Malay Islam. The results show that currently Jawi writing has become a rare commodity in the Indonesian Malay world. While neighboring countries such as Malaysia and Brunei still retain Jawi writing through their use on street names, buildings and other public facilities. The Indonesian Malay world community is more familiar with Latin writing than Jawi writing. Therefore, systematic efforts are needed to reintroduce and maintain the treasury of Jawi writing to the younger generation in the Indonesian Malay world.